1999
DOI: 10.1007/s002800051111
|View full text |Cite
|
Sign up to set email alerts
|

FILM (5-fluorouracil, ifosfamide, leucovorin and mitomycin C), an alternative chemotherapy regimen suitable for the treatment of advanced breast cancer in the `out-patient' setting

Abstract: FILM, a combination of 5-fluorouracil (5-FU) 750 mg/m(2), ifosfamide 1 g/m(2), leucovorin 200 mg/m(2) and mitomycin C 6 mg/m(2) (alternate cycles), was administered to 24 chemo-naive patients with inoperable disease, locally advanced or metastatic. Up to 6 x 3-weekly cycles of FILM were administered on an out-patient basis. Responses included 8 patients in complete remission (CR) and 12 showing a partial response (PR) (83%). Following analysis of these results, the FILM regimen was introduced as a standard out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Initial total response was 83% (CR + PR) among 24 patients. A group of 80 patients could be assessed at 5 years and 56 (70%) remained in remission and 69 (86%) were still alive (67). In a recent phase II study reported from Japan a single high dose of MMC added to CMF was found to enhance relapse free survival in the adjuvant treatment of premenopausal patients (68).…”
Section: Breast Cancermentioning
confidence: 99%
“…Initial total response was 83% (CR + PR) among 24 patients. A group of 80 patients could be assessed at 5 years and 56 (70%) remained in remission and 69 (86%) were still alive (67). In a recent phase II study reported from Japan a single high dose of MMC added to CMF was found to enhance relapse free survival in the adjuvant treatment of premenopausal patients (68).…”
Section: Breast Cancermentioning
confidence: 99%